Overview of Bacterial Diseases in Poultry and policies to control disease and antibiotic resistance - Abdul Samad; Muhammad Hamza; Ayesha Muazzam; Areeb Ahmer; Sania Tariq; Muhammad Junaid Shahid; Muhammad Zain Kaleem; Shehroz Ahmad; Waseem Akram; Fakhar Ul Din (CV. Multi Kreasi Media, 2022)
Bacterial diseases are very common in both man and animals and these are effecting both creatures. Most bacterial Infections are severe enough to kill birds or animals e.g CRD or Mycoplasma infection in birds become the cause of the highest mortality ratio. In this study, we will give a possible solution to combat bacterial infection and also give the Policy to save poultry birds from bacterial infections. This study gives an idea of to alter the antibiotics. This study completely describes the effect of antibiotics and also gives the policy to save the bird from antibiotics resistance. This review shows, if we do the right management we can minimize the risk of bacterial infections the focus of this study is on four things. Describe the Bacterial Diseases Policy to control Bacterial Disease Bring light toward antibiotics resistance Method to reduce antibiotic resistance This study also describes the sign, symptoms, and lesions of disease which may provide a pathway to diagnose the disease, and if a person doesn’t know much about the disease of poultry can also know about the bacterial disease by reading that study